2002
DOI: 10.1074/jbc.m109312200
|View full text |Cite
|
Sign up to set email alerts
|

The Bacillus subtilis Phage φ29 Protein p16.7, Involved in φ29 DNA Replication, Is a Membrane-localized Single-stranded DNA-binding Protein

Abstract: The functional role of the 29-encoded integral membrane protein p16.7 in phage DNA replication was studied using a soluble variant, p16.7A, lacking the N-terminal membrane-spanning domain. Because of the protein-primed mechanism of DNA replication, the bacteriophage 29 replication intermediates contain long stretches of single-stranded DNA (ssDNA Studies on DNA replication and related processes have provided detailed insights in the function of many proteins involved in these processes (for review, see Ref. 1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
25
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 30 publications
0
25
0
Order By: Relevance
“…Gp16.7, which has the potential to bind to both ssDNA and dsDNA, is an integral membrane protein consisting of an N-terminal membrane anchor and a C-terminal cytoplasmic domain. It localizes ϕ29 DNA replication to the membrane (Meijer et al ., 2000, 2001b; Serna-Rico et al ., 2002, 2003). The C-terminal domain of gp16.7 dimerizes in solution but forms larger filaments in the presence of ssDNA (Asensio et al ., 2005; Serna-Rico et al ., 2003).…”
Section: Protein–protein Interactions Of Bacteriophagesmentioning
confidence: 99%
“…Gp16.7, which has the potential to bind to both ssDNA and dsDNA, is an integral membrane protein consisting of an N-terminal membrane anchor and a C-terminal cytoplasmic domain. It localizes ϕ29 DNA replication to the membrane (Meijer et al ., 2000, 2001b; Serna-Rico et al ., 2002, 2003). The C-terminal domain of gp16.7 dimerizes in solution but forms larger filaments in the presence of ssDNA (Asensio et al ., 2005; Serna-Rico et al ., 2003).…”
Section: Protein–protein Interactions Of Bacteriophagesmentioning
confidence: 99%
“…Immunofluorescence studies showed that p16.7 is required for efficient spreading of 29 DNA replication from its initial to additional sites at the membrane of the infected cell (27). In vitro analyses of a soluble p16.7 derivative lacking the membrane anchor revealed that (i) it is a dimer with unspecific DNA binding activity, (ii) it has affinity for the 29 terminal protein, and (iii) it is able to form higher-order multimers upon DNA binding (36,37). The solution and crystal structures of the dimeric functional C-terminal half of p16.7, p16.7C (residues 63 to 130) (32), as well as the crystal structure of p16.7C complexed with double-stranded DNA have been recently solved (1,2).…”
mentioning
confidence: 99%
“…Functional studies showed that p16.7 is involved in the organization of membraneassociated 29 DNA replication and that the efficiency of in vivo 29 DNA replication is affected in its absence (9,13,14). Biochemical studies using a soluble variant lacking the N-terminal membrane anchor, p16.7A, revealed (i) that it has singlestranded DNA (ssDNA) and dsDNA binding activity, (ii) that it is a dimer in solution, and (iii) that it can form oligomers, especially upon DNA binding (13)(14)(15). The p16.7 region following the transmembrane domain (approximately residues 30 -60) forms a low affinity coiled-coil (16).…”
mentioning
confidence: 99%
“…The early expressed 29 gene 16.7 is conserved in all 29-related phages studied so far (9). Protein p16.7 (130 amino acids) is a membrane protein, and its N-terminal transmembrane domain (residues [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] is responsible for membrane localization (13). Functional studies showed that p16.7 is involved in the organization of membraneassociated 29 DNA replication and that the efficiency of in vivo 29 DNA replication is affected in its absence (9,13,14).…”
mentioning
confidence: 99%